2018
DOI: 10.1080/16506073.2018.1490809
|View full text |Cite
|
Sign up to set email alerts
|

Social support, negative social exchange, and response to case formulation-based cognitive behavior therapy

Abstract: We investigated associations between pretreatment social support, negative social exchange, and slope of weekly symptom change for depression, anxiety, and stress over the course of ideographic, case formulation-based, cognitive behavior therapy. Participants were 74 adults treated in a private practice setting. We used self-report measures to assess social support and negative social exchange at intake and to assess symptoms on a weekly basis. At pretreatment, a higher level of social support was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…This finding could be explained through the social exchange theory [ 94 ]. This theory suggests that social interactions can have both positive and negative outcomes, including health-related ones [ 95 , 96 , 97 , 98 ]. In this case, patients with COPD could experience some of their symptoms (such as fatigue, depression, and anxiety) more intensely as a result of negative social interactions and possibly a lack of social support [ 82 , 96 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding could be explained through the social exchange theory [ 94 ]. This theory suggests that social interactions can have both positive and negative outcomes, including health-related ones [ 95 , 96 , 97 , 98 ]. In this case, patients with COPD could experience some of their symptoms (such as fatigue, depression, and anxiety) more intensely as a result of negative social interactions and possibly a lack of social support [ 82 , 96 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…This theory suggests that social interactions can have both positive and negative outcomes, including health-related ones [95][96][97][98]. In this case, patients with COPD could experience some of their symptoms (such as fatigue, depression, and anxiety) more intensely as a result of negative social interactions and possibly a lack of social support [82,96,99]. Therefore, more consideration should be given to social support in future research and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Second, based on the TMIM, uncertainty, and information overload, this study validates the potential adverse effects of social interaction on patient health outcomes on online health platforms. Most studies to date suggest that higher social interaction behaviors are effective in reducing health anxiety (Eidelman et al, 2019; Zeng et al, 2021). In other words, previous research has identified linear benefits of social interaction on health anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…NSE can include hurtful or insensitive comments from friends, family or strangers; hostile interactions between retail workers and customers; and other interactions wherein an individual is yelled at, ridiculed, made fun of or feels taken advantage of. Interactions characterized by NSE are associated with a range of negative physical health symptoms and mental health outcomes, including depression and loneliness (Tsai et al , 2019), PTSD symptom severity (Blais and Zalta, 2023), drug cravings among recovering opioid users (Knapp et al , 2021) and NSE may even impact the rate of symptoms change in cognitive behavioral therapy for depression (Eidelman et al , 2018). Unfortunately, there is a paucity of research examining the role of NSE as a contributor to suicidal thoughts and behaviors (Blais et al , 2021).…”
Section: Negative Social Exchange As a Contributor To Suicidal Ideationmentioning
confidence: 99%